Case Report: Keep your eyes open! Nystagmus guides atypical BPPV - Ludwig, Daniel; Schubert, Michael C. (Frontiers in Rehabilitation Sciences, 2024)
The clinical diagnosis of benign paroxysmal positional vertigo (BPPV) is confirmed from observing the direction, intensity, and duration of nystagmus from unique head positions that advantage gravity to overcome the inertia of otoconia displaced inside the semicircular canals. This case series highlights cases of BPPV with atypical nystagmus presentations relative to the head position. Clinicians should carefully observe symptom and nystagmus presentations regardless of the testing position and utilize technology and rules of vestibular physiology to enhance their diagnostic acumen.